Global, regional, and country-level economic impacts of oral onditions in 2019 - Jevdjevic, Milica; Listl, Stefan (Journal of dental research, 2025)
The recent World Health Organization (WHO) Oral Health Resolution and the subsequent WHO Global Oral Health Action Plan highlight the key relevance of providing information on the economic impacts of oral conditions. The purpose of this study was to provide updated estimates for the global, regional, and country-level economic impacts of oral conditions in 2019. Extending previously established methods, dental expenditures (costs for treatments) and productivity losses for 5 oral conditions (caries in deciduous and permanent teeth, periodontitis, edentulism, other oral diseases) were estimated for the year 2019. The estimated total worldwide economic impacts of oral conditions in 2019 were US $710B, of which US $387B (US $327B to US $404B) was due to direct costs and US $323B (US $186 to US $460) was due to productivity losses for the 5 main oral conditions. Low-income countries spent an average of US $0.52 (US $0.22 to US $0.96) per capita on dental care, while high-income countries spent an average of US $260 (US $257 to US $268) per capita—a 500-fold difference. These findings suggest that oral conditions continue to substantiate an enormous economic burden to individuals and society. The comprehensiveness of estimates supersedes that of previous work as the primary information on direct costs was identified for a larger number of countries. The need for more and better routine reporting and monitoring of the economic impact of oral conditions is emphasized. The relevance of such information is also highlighted by its inclusion in the first-ever WHO Global Oral Health Status Report and Global Strategy on Oral health 2023 to 2030. Given the persistently high economic burden of oral conditions, there is a key role for better prioritization of cost-efficient oral health programs as well as needs-responsive capacity planning.
Online veröffentlicht: 13. November 2024
Gesehen am 15.05.2025